“My Kingdom for a Barking Dog!” - Bert Theunissen (Humanimalia)
According to Raymond and Lorna Coppinger, experts in canine behaviour, sheepdog trialling with Border Collies is mostly for fun. The British International Sheep Dog Society (ISDS), however, contends that trialling has the practical aim of improving  the collie as a working dog. So who is right? I take a historical approach to answer this question, using the wealth of data contained in The Field, a magazine established in 1853, to investigate the sport’s history and relation to practical shepherding.